A study on variable geometries and component matching of variable cycle engine for aircraft with supercruise capability - Karuppiah, Saravanan; Pilidis, Pericles; Sampath, Suresh; Muthuveerappan, N (American Institute of Aeronautics and Astronautics (AIAA), 2023)
The main aim of this work is to investigate variable cycle concept for combat aircraft with super cruise capability. In particular, this study investigates impact of different variable geometry mechanisms and components of aero-gas turbine engine on variable cycle characteristics. This work essentially involves engine cycle modeling and variable geometry control study in order to identify the performance benefits of variable cycle concept. Extensive literature survey is carried out before establishing investigation method and analysis procedure for this research. Single bypass architecture is adopted for this research as it offers easier implementation and yet represents variable cycle concept in complete sense. Hence, conventional mixed flow turbofan engine with bypass ratio of 0.5 is modeled with TURBOMATCH as a baseline configuration for this study. After design point calculation to estimate design point size data and key performance parameters, simulation model is modified in order to investigate the effect of different variable geometries such as bypass mixer, core mixer, nozzle throat and low pressure turbine separately as well as in combination in some cases. A further study is also performed to minimize component losses in order to gain full benefits of cycle effect. From this study, it is found that opening of nozzle is having the largest effect on expanding bypass ratio (2.54 times) and therefore results in lowest fuel consumption. Partial closure of bypass mixer with partial opening of nozzle is turned out be best control schedule for achieving maximum specific thrust. Low pressure turbine NGV variability has a potential to vary the bypass ratio in the range of 0.3-0.75 from design point BPR of 0.5,while modulation of flow capacity in vane-less LPT only results in around 6-7% change in BPR.